2019
DOI: 10.3390/su11205708
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Relationship between Price Mechanism and Short-Term Behavior in Chinese Farmland Trusteeships

Abstract: After the policy of separating ownership rights, contract rights, and management rights to rural land, some Chinese farmers entrusted their land to agricultural social service providers. However, at present in land trusteeships, short-term behaviors exist, which are not good for the sustainable utilization of land. This article uses a dynamic game model to analyze the economic reasons for short-term behavior and to explore possible mechanisms. The study's results showed that fluctuations in trusteeship prices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The market regulation function of the government cannot be ignored [55]. In fact, government-led agricultural services are effective for developing countries [56], since private enterprises mainly pursue market value, peasants must spend a high price if they want to obtain good services, which are not suitable for the sustainable development of agriculture [57].…”
Section: Peasants' Participation Intention Behavior and Policy Supportmentioning
confidence: 99%
“…The market regulation function of the government cannot be ignored [55]. In fact, government-led agricultural services are effective for developing countries [56], since private enterprises mainly pursue market value, peasants must spend a high price if they want to obtain good services, which are not suitable for the sustainable development of agriculture [57].…”
Section: Peasants' Participation Intention Behavior and Policy Supportmentioning
confidence: 99%
“…Relying on service organizations to adopt agricultural production trusteeship is an important way to promote the precise connection between modern agricultural green development and green transformation for farmers [21,22]. Trusteeship refers to a socialized service model in which farmers entrust the partial or whole process of agricultural production, including planting, management and harvesting, to agricultural production service institutions without transferring land management rights [23]. Combined with the concept of agricultural green development, the whole trusteeship of green agricultural production is a model in which the service subjects use green production technology to complete the whole process of agricultural production entrusted by farmers and other subjects in a relatively low-cost manner.…”
Section: Introductionmentioning
confidence: 99%
“…found that the source of service information is an important influencing factor, and members of cooperatives tend to choose the purchasing and selling services of agricultural supplies. In the case of information asymmetry, the service price and surrounding people's behaviors will significantly affect the decision of farmers to sign services [14]; the short-term service purchased by farmers out of prudence will affect the service quality and the interests of both service subjects [15]; and the service subject's reduction in service quality and farmers' excessive supervision will result in bilateral moral hazard [16]. The cooperation between service subjects and family farms not only achieves a high coverage rate of agricultural productive service land, but also collects state subsidies, which fails to fundamentally solve the needs of small farmers' land trusteeship [17].…”
Section: Introductionmentioning
confidence: 99%